Experimental characterization of a prototype detector system for carbon ion radiography and tomography - Rinaldi, Ilaria; Brons, Stephan; Gordon, J.; Panse, Ralf; Voss, B.; Jäkel, Oliver; Parodi, K. (Physics in medicine and biology, 2013)
Ion beams exhibit a finite range and an inverted depth-dose profile, the Bragg peak. These favorable physical properties allow excellent tumor-dose conformality. However, they introduce sensitivity to range uncertainties. Although these uncertainties are typically taken into account in treatment planning, delivery of the intended dose to the patient has to be ensured daily to prevent underdosage of the tumor or overdosage of surrounding critical structures. Thus, imaging techniques play an increasingly important role for treatment planning and in situ monitoring in ion beam therapy. At the Heidelberg Ion Beam Therapy (HIT) center, a prototype detector system based on a stack of 61 ionization chambers has been assembled for the purpose of radiographic and tomographic imaging of transmitted energetic ions. Its applicability to ion-based transmission imaging was investigated experimentally. An extensive characterization of the set-up in terms of beam parameters and settings of the read-out electronics was performed. Overall, the findings of this work support the potential of an efficient experimental set-up as the range telescope equipped with high sensitivity and fast electronics to perform heavy ion radiography and tomography at HIT.
Gesehen am 12.01.2022